GESTION DES MENAGES PAR DES FEMMES VENDEUSES DES POISSONS A UVIRA - LUPIKI, MBATE; AKOBE, KISUBI (IJRDO - Journal of Business Management, 2021)
In the Democratic Republic of Congo, the state having almost resigned from its responsibilities with regard to the care of public officials and civil servants, the breach has opened up to married women to provide for the financial needs for the survival of households. In addition to this irresponsibility of the Congolese State, in the East of the Republic, there are situations of political crises fueled by the proliferation of armed groups pushing some women in the city of Uvira to draw on their immediate and / or distant environment. means to enable them to cover family needs by supplying themselves with fish by relegating and reallocating their household functions. These relegations and reallocations of household functions by women fish sellers lead to dynamics that operate within their households as well as various consequences.